PENGARUH TEKNOLOGI ARTIFICIAL INTELLIGENCE APLIKASI DUOLINGO TERHADAP KEPUASAN PELANGGAN MENGGUNAKAN METODE TECHNOLOGY ACCEPTANCE MODEL (TAM) - Cesya Catherine; Albert Wijaya; Dicky Pratama (Jurnal Teknologi Informasi dan Komputer, 2026)
The advancement of technology, particularly Artificial Intelligence (AI), has brought significant changes to the education sector, especially in the use of digital learning applications such as Duolingo. This application integrates AI to provide an adaptive and personalized learning experience, enabling content customization and automatic feedback based on user performance. This research endeavors to understand the impact of AI technology in the Duolingo application on user satisfaction by applying the Technology Acceptance Model (TAM) framework. A quantitative approach was used, with data gathered through questionnaires distributed to 100 active Duolingo users. The research variables include perceived ease of use (PEOU), perceived usefulness(PU), attitude toward use(AT), behavioral intention(BI), and actual usage(AU). The outcomes of the validity and reliability tests show that all instruments utilized in this research fulfill the requirements for validity and reliability.Structural model analysis shows that all hypotheses in the TAM model are statistically significant, where the ease of use of AI positively influences perceived usefulness, user attitude, behavioral intention, and actual usage. The conclusion of this study reveals that the integration of AI in Duolingo has a positive impact on user satisfaction. This study helps to further the understanding of learning technology that is more engaging, interactive, effective, and adaptable to future needs.